Surround Sensor Placement and Packaging - Büller, Joar; Eriksson, Wilhelm (My University, 2021)
By improving an already existing system, the user shall be able to view the surroundings of the vessel through a screen to simplify the docking procedure further. This feature is achieved by mounting sensors around the vessel. The task is therefore to develop a mount which enables mounting of the sensors as well as to investigate the most suitable placements for optimal sensor coverage. Initially a market research was carried out to find out if similar concepts already exist. Effort was also put into retrieving data for the specific sensors that were going to be utilized. The research and collected data were used to create a list of requirements and a function analysis. Since the client needed a mount earlier than expected several steps of product development were omitted in order to save time. Based on previous research two preliminary concepts were developed immediately, whereof one was determined to be further developed. After several reviews and evaluations, a mount was eventually manufactured. Simultaneously the placement of the sensors was investigated. The thesis resulted in a functioning mount with several possibilities of adjustment to achieve satisfying sensor coverage of the marine vessel. Future developments and improvements were also explored and presented. For the thesis work the type of sensors that were ought to be utilized was given by the client. The thesis was defined to only construct and design a mount for the given sensors